Tantangan Pengendalian Diabetes Melitus dan Hipertensi pada Lansia: Sebuah Laporan Kasus - Fayza Syachrani; Dian Isti Anggraini (CV. Jasa Sukses Abadi, 2026)
Diabetes mellitus (DM) and hypertension are common chronic diseases among older adults and frequently coexist, increasing the risk of cardiovascular and microvascular complications. Successful disease management depends not only on pharmacological treatment but also on dietary habits, physical activity, and medication adherence. This case report describes a 60-year-old woman with a 15-year history of DM and hypertension who attended a routine evaluation at an elderly community health service. Her initial assessment revealed a blood pressure of 168/96 mmHg, a random blood glucose level of 263 mg/dL, and a body mass index of 21 kg/m². The patient reported a high-sodium diet, frequent consumption of fried foods, low-fiber carbohydrate intake, limited physical activity, and poor medication adherence due to forgetfulness and limited access to healthcare services. She received education regarding medication adherence, balanced nutrition, sodium and fat restriction, increased physical activity, and the importance of regular follow-up. Three weeks later, her blood pressure decreased to 160/90 mmHg and her random blood glucose level improved to 190 mg/dL, although therapeutic targets had not yet been achieved. This case highlights that inappropriate dietary habits and poor medication adherence contribute to suboptimal control of DM and hypertension in older adults. A comprehensive approach involving continuous education, lifestyle modification, adherence assessment, and regular monitoring is essential to improve long-term therapeutic outcomes and prevent disease-related complications.